Percentage birth weight loss and hyperbilirubinemia during the first week of life in term newborns - S. A. K. Indriyani; I Wayan Retayasa; Achmad Surjono; Purnomo Suryantoro (Paediatrica Indonesiana, 2009)
Background Hyperbilirubinemia is the most common problem interm newborns during the first week of life. Hyperbilirubinemiain term newborns without other risk factors is usually causedby dehydration and reduced calorie intake that is marked byexcessive weight loss.Objective To determine the relationship between percentage birthweight loss and hyperbilirubinemia during the first week of lifein term newborns.Methods A cross sectional study was conducted at the Departmentof Child Health, Medical School, Udayana University, SanglahHospital, Denpasar, Indonesia. The weight of term newbornswas measured on the first, third, and seventh day after birth.In addition, a complete blood count, reticulocyte count, andperipheral blood smear, were carried out on the first day. Serumbilirubin level was measured on the first, third, and seventh day.Clinical signs, jaundice, type and frequency of intake, and timeof meconium transit were followed during the stay in hospital.Linear regression, correlation, and logistic regression analysis wereperformed to determine variables related to hyperbilirubinemia.Results 68 newborns were enrolled in this study, with 7 developedhyperbilirubinemia by the third day. There was a significant(P<0.001) but weak to moderate correlation (r = 0.39)between percentage birth weight loss and total serum bilirubinconcentration on the third day. Logistic regression analysisshowed that percentage birth weight loss on the third day wassignificantly related to hyperbilirubinemia [OR 38.18 (95% CI2.29 to 637.61), P=0.011].Conclusion Percentage birth weight loss is related to hyperbilirubinemiain term newborn during the first week of life.